God and the Nation after the Yom Kippur War:: Giluy Eliyahu by S. Yizhar - Dekel, Yael (MiKAN, 2017)
As is evident by its title, which draws from the Jewish post-biblical tradition ofthe Revelation of Elijah, Yizhar's novel Giluy Eliyahu (1999) presents numerous divine revelations. In this article Dekel argues that throughout his novel, Yizhar re-establishes the theological in order to deal with the trauma of the Yom Kippur War and to enable the nation to move towards the future as a unified whole. This theological revelation is the starting point for reconstructing an analogy between the theological and the political, as famously argued by Carl Schmitt. After examining political theology as present in the novel, this article demonstrates how the analogy of theology and politics is carried out in the novel on the grounds of mythology, in the sense demonstrated by Roland Barthes in his essay Myth Today.